Effects of electromagnetic field on proliferation, differentiation, and mineralization of MC3T3 cells - Teoh, Swee-Hin (2019)
The steep increasing incidence of bone diseases and fractures provides a commanding impetus and growing demands for bone tissue engineering research. Pulsed electromagnetic fields (PEMFs) have been documented to promote bone fracture healing in nonunions and to enhance the maturation of osteoblastic cell, which is the key element in bone tissues. However, the optimal parameters for PEMF stimulation are still being explored. In this study, we investigated the effects of PEMF treatment on the proliferation, differentiation, and mineralization of osteoblast precursor cells MC3T3-E1 to explore the cell growth profile under different PEMF exposure durations (15, 30, and 60 min daily) with a magnetic field strength of 0.6 mT, at a frequency of 50 Hz, and cultured in media with or without osteogenic supplements for 28 days. Cell viability and metabolic activity were accessed by confocal microscopy, and alamarBlue time-course measurements and results indicated that there were no adverse effects under designated PEMF condition. After 7 days of PEMF exposure, in comparison with negative controls, cell numbers increased when exposed to PEMF in culture medium and were independent of osteogenic supplements. However, PEMF might not have significant impact on cellular mineralization as observed from calcium deposition analysis, even though osteogenic gene expression was upregulated for cells with PEMF exposure. Von Kossa and Alizarin Red staining indicated that extracellular matrix mineralization occurred at day 28 with osteogenic supplements only, and no significant differences were found among those samples with different PEMF treatment durations. In summary, our results suggested that PEMF stimulation for as short as 15 min could improve cell proliferation but not mineralization in vitro. Thus, this study highlights the importance of choosing appropriate PEMF parameters to achieve the desired effect on target cells. The optimization of PEMFs will enhance the efficiency of its usage as a clinical, adjuvant therapeutic treatment for bone defect regeneration. Impact Statement We present the study about how the parameters of pulsed electromagnetic field (PEMF) stimulus affected calvarial osteoblast precursor cell in terms of growth, viability, and differentiation. This research provides insight and foundation to clinical application of noninvasive therapy using PEMF to improve bone regeneration.